Evaluation of the breeding strategy for milk yield of Holstein Friesian cows on large scale dairy farms in Malawi - Chagunda, Mizeck G.G.; Bruns, E.W.; King, J.M.; Wollny, C.B.A. (Cambridge University Press, 2004)
Over the last two decades, dairy cattle management in Malawi has been oriented towards increasing milk yield per animal. One consequence of this process has been reliance on Holstein Friesian bull semen from temperate regions. The aim of the current study was to evaluate the performance of Holstein Friesian cows on large-scale farms in Malawi. A data set of 60 640 test-day records from Holstein Friesian cows in first, second and third lactation from three large-scale dairies in Malawi were utilized. Fixed effects of herd, year and season of calving were tested. (Co)variance components were estimated through the restricted maximum likelihood (REML) procedure. Heritability, genetic and phenotypic correlations for milk yield, lactation length, age at first calving, and calving interval were determined. In general, milk yield decreased over the years and there was significant (P<0.001) variation in milk yield between herds. The genetic base, as indicated by the genetic trend, remained almost constant in the studied period. This entails genotype by environment interaction, culminating in the additive genetic effect not expressing itself fully in the phenotype. It is therefore apparent that considerable improvement could be achieved by improving the production environment.